Prevalence and Complications of Hypothyroidism in Pregnancy - Marzieh Lotfalizadeh; Nayereh Ghomian; Mansoureh Mohammad Nezhad (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2017)
Introduction: Thyroid disorders are common in young women. Hypothyroidism has a broad clinical range of subclinical to severe disease along with various complications. Hypothyroidism in pregnancy causes many complications on pregnancy. Considering the contradictory results in this regard, this study was performed with aim to evaluate the prevalence of subclinical hypothyroidism and compare the complications of this disease in patients treated with or without levothyroxine. Methods: This cross-sectional and interventional study was conducted on 1,000 pregnant women who referred to Prenatal Clinic of Imam Reza Hospital and the clinics of two gynecologist colleagues in Mashhad in 2012-2013. 212 women with TSH > 3 in the first trimester of pregnancy were selected and randomly divided into intervention (n=112) and control (n = 100) groups. Individuals in the intervention group received 0.5 to 1.5 pills of levothyroxine from diagnosis until delivery. Patients were monitored until the end of pregnancy and complications of pregnancy were evaluated between the two groups. Data were analyzed using SPSS software (version 11.5), Chi-square and independent t-test. P < 0.05 was considered significant. Results: In this study, the prevalence of hypothyroidism was 21%. Based on Chi-square test, two groups did not show significant difference in terms of abortion, preeclampsia, preterm labor, Apgar score less than 7, and need for NICU admission (p>0.05). However, there was a significant difference between the two groups in terms of abruption, (P=0.015) and abruption was higher in untreated group. Based on the independent t-test, the weight of newborns was higher in the treated group and the two groups were significantly different (P=0.025). Conclusion: Hypothyroidism is a common disease in pregnancy and TSH is a prerequisite for pregnancy testing in order to prevent its complications when diagnosed.